(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The Arabic language is renowned for its lexical richness, particularly in the domain of near-synonyms (اللغوية الفروق). This paper examines the semantic distinctions among five Arabic verbs that are commonly translated as «to come» in English: jaʼa (جاء), ata (أتى), aqbala (أقبل), ḥaḍara (حضر), and qadima (قدم). Drawing upon classical Arabic lexicography, Qurʼanic usage, and modern linguistic scholarship, the study employs a comparative analytical method to identify the distinctive semantic features, pragmatic contexts, and stylistic nuances of each verb. The findings reveal that despite their apparent synonymy, each verb carries unique connotations related to manner, purpose, distance, formality, and aspectual perspective. The study contributes to the field of Arabic lexical semantics and has implications for Qurʼanic exegesis, Arabic language pedagogy, and translation studies.